Diseminasi Program Belajar Merdeka Kampus Merdeka (MBKM) Untuk Meningkatkan Peran Mahasiswa Fakultas Sains Teknologi Dan Desain Universitas Trilogi Di Bidang Penelitian Dan Pengabdian Masyarakat - Yodfiatfinda Yodfiatfinda; Silvester Dian Handy Permana; Dina Nurul Fitria (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
Advances in technology and its applications have entered into all aspects of life. There are almost no fields that are not affected, on the one hand it creates business efficiency and on the other it becomes a disruption marked by the loss of various types of work because they are replaced by automated systems and machines. This phenomenon makes the dynamics of the world of work increasingly competitive. The world of higher education which is the outlet for the birth of educated and skilled workers must adapt. One of the efforts made is to provide flexibility for students to gain experience and knowledge in accordance with their passion. This flexibility is the independent campus learning program initiated by the Ministry of Education and Culture. This study aims to determine the level of knowledge of the students of the Faculty of Science, Technology and Design towards the MBKM program to increase the role of students in the fields of research and community service. The method used is descriptive analysis. Respondents were determined based on a non-purposive sampling technique, namely sending questionnaires to all students and the respondents were students who sent answers. In general, FSTD students are interested in joining the MBKM program. The majority want the value of the MBKM program to be equivalent to 20 credits. Respondents from FSTD students obtained information from the Ministry of Education and Culture's website, the desired form was internship/PKL, this program is also believed not to extend the study period, the main obstacle mentioned is cost. Most students believe that studying outside the study program will get additional skills and improve soft skills.Keywords: MBKM Program; Disruption; Study; Trilogy University Abstrak:Kemajuan teknologi dan aplikasinya telah masuk ke semua aspek kehidupan. Hampir tidak ada bidang yang tidak terdampak, di satu sisi memunculkan efisiensi usaha dan di sisi lain menjadi disrupsi yang ditandai hilangnya berbagai jenis pekerjaan karena digantikan oleh sistem maupun mesin otomasi.  Fenomena tersebut menjadikan dinamika persaingan dunia kerja semakin ketat.  Dunia pendidikan tinggi yang menjadi outlet lahirnya tenaga-tenaga terdidik dan terampil harus menyesuaikan diri.  Salah satu upaya yang dilakukan ialah memberikan keleluasaan bagi mahasiswa untuk menimba pengalaman dan ilmu yang sesuai dengan passion nya.  Keleluasaan tersebut ialah program merdeka belajar kampus merdeka yang dicetuskan ole Kementerian Pendidikan dan Kedbudayaan.  Penelitian ini bertujuan untuk mengetahui tingkat pengetahuan mahasiswa Fakultas Sains Teknologi dan Desain terhadap program MBKM untuk meningkatkan peran mahasiswa di bidang penelitian dan pengabdian masyarakat. Metode yang digunakan ialah analisis deskriptif.  Responden ditentukan berdasarkan teknik non purposive sampling, yaitu mengirimkan kuisioner kepada seluruh mahasiswa dan yang menjadi responden ialah mahasiswa yang mengirimkan jawaban. Secara umum mahasiswa FSTD tertarik untuk mengikuti program MBKM. Mayoritas ingin nilai program MBKM setara dengan 20 SKS. Responden mahasiswa FSTD memperoleh informasi dari website Kemendikbud, bentuk yang diinginkan adalah magang/PKL, program ini juga dipercaya tidak memperpanjang masa studi, kendala yang disebutkan utamanya ialah biaya.  Sebagian besar mahasiswa yakin bahwa belajar di luar prodi akan mendapat ketermapilan tambahan dana meningkatkan softskill.Keywords: Program MBKM; Disrupsi; Penelitian; Universitas Trilogi